An evaluation of the performance of the Dynamiker® Fungus (1-3)-β-D-Glucan Assay to assist in the diagnosis of invasive aspergillosis, invasive candidiasis and Pneumocystis pneumonia. (3rd March 2017) - White, P. Lewis; Price, Jessica S.; Posso, Raquel B.; Barnes, Rosemary A.
Abstract: Invasive fungal disease (IFD) can be caused by a range of pathogens. Conventional diagnosis has the capacity to detect most causes of IFD, but poor performance limits impact. The introduction of non-culture diagnostics, including the detection of (1-3)-β-D-Glucan (BDG), has shown promising performance for the detection of IFD in variety of clinical settings. Recently, the Dynamiker® Fungus (1-3)-β-D-Glucan assay (D-BDG) was released as an IFD diagnostic test. This article describes an evaluation of the D-BDG assay for the diagnosis of invasive aspergillosis (IA), invasive candidiasis (IC) and Pneumocystis pneumonia (PCP) across several high-risk patient cohorts and provides comparative data with the Associates of Cape Cod Fungitell ® and BioRad Platelia™ Aspergillus Ag (GM) assays. There were 163 serum samples from 121 patients tested, from 21 probable IA cases, 28 proven IC cases, six probable PCP cases, one probable IFD case, 14 possible IFD cases and 64 control patients. For proven/probable IFD the mean BDG concentration was 209pg/ml, significantly greater than the control population (73pg/ml; P : <.0001). The sensitivity, specificity, and diagnostic odds ratio for proven/probable IFD was 81.4%, 78.1%, and 15.5, respectively. Significant BDG false positivity (9/13) was associated post abdominal surgery. D-BDG showed fair and good agreement with the Fungitell ®, and GM assays, respectively. In conclusion, the D-BDG provides a useful adjunct test to aid the diagnosis of IFD, with technical flexibility that will assist laboratories processing low sample numbers. Further, large scale, prospective evaluation is required to confirm the clinical validity and determine clinical utility.